Considerações sobre o emprego da anáfora nominal em textos de alunos - Figueiredo, Olívia Maria (2001)
This study a study of nominal anaphora is presented from a linguistic, discursive and didactic perspective. Particular attention is paid to the use of anaphora in regard to the different types of text and the degree of cognitive devclopment ofthe subject in the learning situation. The author concludes that the value of the cohesion of nominal anaphora is due to its capacity to r20090220intain the linguistic antecedent active in the operative memory (and its consequent integration in the representation which is being constructed on the contents of the text).